2015
DOI: 10.1007/978-3-319-19243-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Designing Software Ecosystems: How to Develop Sustainable Collaborations?

Abstract: Abstract. It has become an increasingly common practice that software companies collaborate with external developers to develop a software platform for a shared market, constituting software ecosystems. One main concern in adopting the practice of software ecosystem is how to attract external developers to a platform, and how to establish sustainable collaborative relationships with them. We discuss that explicating and in-depth analysis of developers' objectives and decision criteria can facilitate the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Today, only the more radical approaches still pursue this line of inquiry (e.g., Vercellone, 2015;Morozov, 2019). For more mainstream economists, the relationship between commons-based and market-oriented production has become more central, as many commercial firms both contribute to the digital commons and are using Common Pool Resources in their commercial strategies (Sadi et al, 2015). The aim is to develop "open strategies", which is integrating commons-based production and various kinds of crowd-based inputs into company management (Birkinshaw, 2017).…”
Section: Economics New Models Of Productionmentioning
confidence: 99%
“…Today, only the more radical approaches still pursue this line of inquiry (e.g., Vercellone, 2015;Morozov, 2019). For more mainstream economists, the relationship between commons-based and market-oriented production has become more central, as many commercial firms both contribute to the digital commons and are using Common Pool Resources in their commercial strategies (Sadi et al, 2015). The aim is to develop "open strategies", which is integrating commons-based production and various kinds of crowd-based inputs into company management (Birkinshaw, 2017).…”
Section: Economics New Models Of Productionmentioning
confidence: 99%
“…In addition, the work does not focus on developers. Sadi et al (2015) proposed a generic approach based on Android and iOS ecosystems to identify types of developers and derive alternative solutions to design appropriate collaboration. For example, the authors have found that Android platform developers choose an open source platform to cultivate intrinsic motivations such as skill development and reputation enhancement.…”
Section: Stack Overflowmentioning
confidence: 99%
“…Emergent stakeholders play a major role in driving requirements discussion and decision making. To our knowledge, however, research has so far mainly investigated emergent developers [46,24,51] and emergent knowledge [59], while only few works exist that start to investigate the effect of emergent contributors on requirements [35]. This is however an important aspect, as software ecosystems facilitate communication between the various levels of involved organizations and the role of emergent collaboration spans beyond developers and software teams [33].…”
Section: Related Workmentioning
confidence: 99%